PEMAHAMAN KARAKTER WISATAWAN RUSIA DALAM INDUSTRI PARIWISATA BALI - Ginaya, Gede (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2010)
Bali is regarded as one of the most interesting places as a tourist destination, which is very frequently visited by tourists from all over the world. One of the recent phenomena in Balinese tourism is marked by the significant increasing number of Russian tourists. In regards to this matter; oil stakeholders should be ready in giving the maximum services in order to maximaize the business opportunity. The purpose of this study is to find out a clear picture of the characters of the Russian tourists which can influence services given to satisfy the needs and expectation of the tourists themselves. The understanding of the character of Russian tourists is really needed for bridging the cultural gap resulted from the interaction activity of giving services to the tourists. Consequently, the indicator of the service quality in the tourism industry can be realized in the form of satisfaction and positive impression from the given services.